Impacts of a Non-indigenous Ecosystem Engineer, the American Beaver (Castor canadensis), in a Biodiversity Hotspot - Richmond, Jonathan Q.; Swift, Camm C.; Wake, Thomas A.; Brehme, Cheryl S.; Preston, Kristine L.; Kus, Barbara E.; Ervin, Edward L.; Tremor, Scott; Matsuda, Tritia; Fisher, Robert N. (Frontiers in Conservation Science, 2021)
Non-native species having high per capita impacts in invaded communities are those that modulate resource availability and alter disturbance regimes in ways that are biologically incompatible with the native biota. In areas where it has been introduced by humans, American beaver (Castor canadensis) is an iconic example of such species due to its capacity to alter trophic dynamics of entire ecosystems and create new invasional pathways for other non-native species. The species is problematic in several watersheds within the Southern California-Northern Baja California Coast Ecoregion, a recognized hotspot of biodiversity, due to its ability to modify habitat in ways that favor invasive predators and competitors over the regions’ native species and habitat. Beaver was deliberately introduced across California in the mid-1900s and generally accepted as non-native to the region up to the early 2000s; however, articles promoting the idea that beaver may be a natural resident have gained traction in recent years, due in large part to the species’ charismatic nature rather than by presentation of sound evidence. Here, we discuss the problems associated with beaver disturbance and its effects on conserving the region’s native fauna and flora. We refute arguments underlying the claim that beaver is native to region, and review paleontological, zooarchaeological, and historical survey data from renowned field biologists and naturalists over the past ~160 years to show that no evidence exists that beaver arrived by any means other than deliberate human introduction. Managing this ecosystem engineer has potential to reduce the richness and abundance of other non-native species simply because the novel, engineered habitat now supporting these species would diminish in occupied watersheds. At the same time, hydrologic functionality would shift toward more natural, ephemeral conditions that favor the regions’ native species while suppressing the dominance of the most insidious invaders.